Reading Comprehension Strategies and Difficulties among Learners at Tertiary Level in Bangladesh - Aklima Bintay Ahmed (Transpublika Publisher, 2026)
Reading comprehension difficulties are a matter of concern for undergraduates at the tertiary level in Bangladesh. This paper seeks to determine the sorts of issues that undergraduates face while reading comprehension. Both primary and secondary data would be used for this research. The findings show that student performance on reading comprehension assessments in the classroom is moderately satisfactory. It is concerning that many students are unable to acquire this ability. Students’ perceptions of their reading abilities are inadequate since many of them strain to communicate fluently. Additionally, they suffer to pass the reading exam since they don’t routinely read newspapers to hone their reading abilities. Some have trouble trying to predict the meaning of a text, which is a negative reflection of their reading proficiency. Lastly, it also highlights a few techniques for enhancing the abilities. Teachers employ studying comprehension approaches as a guidance tool to help students become strategic readers. It will help students build the information, abilities, and procedures necessary to become strategic readers.